Investimento obrigatório em P&D em contratos de concessão de serviços públicos de transporte ferroviário: estímulo ou entrave para inovação? - Cibele Bersan Mariano Pádua (2024)
This dissertation consists of the investigation and evaluation of the normative framework that governs the mandatory R&D Program established by the National Land Transport Agency (NLTA), aimed at railway transport service concessionaires, in order to know whether or not it represents an instrument of stimulus to innovation. The discussion is important, because promoting innovation in regulated sectors that constitute true natural monopolies, such as the railway sector, is not an easy task. Furthermore, the mandatory R&D Program is in the process of being implemented and appears to have ignored the discussion and evolution of other mandatory R&D Programs established by the National Petroleum Agency (ANP) and the National Electric Energy Agency (NEEA). The Program also seems not to have followed all the normative evolution that the Science, Technology and Innovation (ST&I) theme in Brazil has recently undergone, whether through the edition of Constitutional Amendment n. 85/2015, through the implementation of the Legal Framework for ST&I, the Legal Framework of Startups and, more recently, the edition of the new Bidding Law. To highlight the drawbacks of this new mandatory R&D Program, two summary tables were created: one that compares the general aspects of the main mandatory R&D Programs established in the country and another that consolidates all suggestions for improvement to the NLTA railways R&D Program. To this end, a qualitative methodology was used, with emphasis on bibliographical review and documentary analysis, especially analyzing the normative framework that constitutes the regulation of expenditure on R&D by railway transport concessionaires and concessionaires in the road, electricity, and oil gas sectors.